Good Samaritans - García Lozano, Francisco José (Razón y fe, 2018)
The current proposals for a "Samaritan culture" arise from the desire to complement and accompany realities that, in terms of social and market logics, are invisible or uncomfortable, and require the adoption of more concrete behaviors for attention, solidarity, closeness and empathy. Messages that invite us to regain hope and optimism in human beings are welcome, and that show that there is still room for goodness and solidarity in the world. The films of the Belgian brothers Dardenne and the Finnish director Aki Kaurismäki are two examples of how good cinema and social commitment are not opposing terms. Film for those who want to see beyond themselves.